Employment Agreement in the Civil Code BW and KHES: Concept, Arrangements, and Contract Format - Asep Sahputra; Alfatunisah; Ananda Luk-luk I’lmunawarah Sitorus; Habib Fahrezi Tanjung; Athaya Sitepu (ISNU Sumatera Utara, 2025)
An employment agreement is a fundamental form of contract in civil law, both regulated by the Civil Code (KUHPerdata) and the Sharia Economic Law Code (KHES). Drafting a sound and comprehensive contract is crucial to prevent potential future disputes and provide legal certainty for all parties involved. In this study, the researcher used two approaches: normative juridical. This approach serves to inventory applicable laws and regulations and various relevant legal theories. Drafting a written employment agreement is crucial, encompassing essential elements such as the identities of the parties, job descriptions, remuneration, and the implementation period. This step aims to ensure legal certainty and minimize the possibility of future disputes. Employment agreements, whether drafted based on the provisions of Law Number 13 of 2003 or the sharia principles in the KHES, play a significant role in creating fair, transparent, and regulatory-compliant employment relationships. Furthermore, the application of Sharia principles such as fairness, honesty, and the prohibition of usury in employment contracts will further strengthen harmonious relations between employees and employers in the modern business context. Therefore, it is crucial for all parties involved to pay close attention to these aspects to foster a working relationship based on trust, fairness, and compliance with applicable laws.